SIGNIFICANCE OF PROJECT MANAGEMENT SKILLS AND BALANCING OF MANAGERIAL CONFLICTS BETWEEN PROJECT STAKEHOLDERS - Netto, Joshua; Raju, Valliappan (PEOPLE: International Journal of Social Sciences, 2017)
As the business environment in the building and construction industry becomes increasingly competitive with a high importance on efficiency and productivity, it is significant for project management teams to develop the right skills and competencies to handle projects well in order to balance the differing-needs of their key stakeholders. The critical part is the subject of project stakeholder satisfaction that Weaver (2007, p. 20-21) mentions as the objective of project management, which links all the competencies of the project manager, the human management factor, and the importance of leading the project with the drive to achieve completion “as efficiently as possible, to the satisfaction of the project’s stakeholders. As a result, achieving key project stakeholder satisfaction appears mysterious due to the subjectivity of the defining success because project success is “perceived differently by different stakeholders” (Shokri-Ghasabeh & Kavousi-Chabok, 2009). The client on one hand, being the paymaster for the project measures success in terms of the delivery of value. The consultants, on the other hand, have a deep interest in their reputation as designers protect the interests and needs of their clients as their hired agent. The contractors, in contrast, often choose to participate in a project based on the client’s financial capabilities, and have interest to call the designs and the completeness of contract documents into question, since variations present opportunities to make additional profit, or to incur losses on the part of the contractor should these not be put forward. In view of this the leadership, management capabilities and communication skills of the project manager and the project management team is critical, which includes interpersonal skills through negotiations, expectations management, influencing problem solving and decision-making skills in order to delicately balance the needs and expectations of these stakeholders, complete the project, and gain acceptance of the deliverable to the stakeholder’s satisfaction at the close out of the project. This research paper studies and describes about the relationship between constructor, client and consultant in project management perspective.